Optimization of Mobile SIM for Satpas 1221 Depok Metro Police in SIM Administration Services in 2020 - Verren Vinayaka Deva Wewengkang (Advances in Police Science Research Journal, 2021)
The Depok Traffic Unit has a mobile SIM booth for Satpas 1221 as the operator of SIM administration services, which functions as a means of public service for the National Police in the areas of registration and identification of motorized vehicles, drivers and traffic education. Nowadays people often demand quality public services, but public services so far are still expensive, slow, convoluted and seem not the people who receive the services but the people themselves who provide the services. Therefore, the SIM extension service carried out by the Satpas 1221 Mobile SIM outlet seeks to improve the quality of excellent service and change the perspective of the community. In discussing this research, the author uses the theory of Public Service Management, FFA theory, the concept of public service, and the concept of Mobile SIM Services to discuss the findings and research problems. This study uses a qualitative approach. The focus of the research is on administrative services for the SIM Satpas 1221 Polres Metro Depok with members and officers of the Mobile SIM Depok city as a source of document data, then the validity of the data is proven by data triangulation. Data analysis techniques in the form of data reduction, data presentation and drawing conclusions. The results of the research conducted by the authors found that Satpas 1221 had made various efforts to improve public services, but in practice there were still several factors that influenced the implementation of mobile SIM service activities by Satpas 1221 Polres Metro Depok. Based on the results of the study, the authors suggest improving service quality, fulfilling facilities and infrastructure that support mobile SIM operations during the pandemic, expanding the platform so that those who get facilities can be evenly distributed and working with the media for the implementation of mobile SIM socialization carried out by Satpas 1221 Depok. .